Portfolio Asset Allocation Decisions: A Meta-Analysis - Gusni Gusni; Nugraha Nugraha (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
Portfolio asset allocation decisions are not passive as mention in the modern portfolio theory, because many factors that can influence it. The purpose of this study is to explain the portfolio asset allocation decisions based on the results of previous research studies by using a meta-analysis approach. The meta-analysis was carried out from a systematic review of the literature review. This study uses secondary data gathered from the various reputable journal by using 14 relevance research that has been published for the period of 2005 – 2019. The result explains that various empirical evidence of many studies on portfolio asset allocation decisions systematically can provide an overview of research trends and types of research conducted by researchers. Most of the studies are quantitative research, use a more behavioral approach, and provide new insights related to factors that can influence investors in making portfolio asset allocation decisions